TRANSFORMASI MANAJEMEN KEPEMIMPINAN PENDIDIKAN DALAM PERSPEKTIF KEPEMIMPINAN VISIONER - Siswadi, Siswadi (Jurnal Manajemen Pendidikan, 2023)
The transformation of educational leadership management has become an urgent necessity in responding to global dynamics characterized by technological advancement, social complexity, and increasing demands for educational quality. This article aims to conceptually examine how the transformation of educational leadership management can be understood from the perspective of visionary leadership. The study employs a qualitative approach using a literature review method, analyzing various academic sources to identify relevant leadership patterns, concepts, and strategies. The findings reveal that visionary leadership plays a strategic role in directing organizational change through the formulation of clear visions, adaptability to change, and the strengthening of innovative and collaborative values. The transformation of leadership management is not only related to administrative aspects but also involves a paradigm shift from structural orientation to a transformative approach focused on human resource development. Visionary leadership serves as a driving force in creating a progressive, responsive, and sustainable organizational culture. Therefore, the integration of leadership management and visionary perspectives is essential in enhancing educational quality in a holistic and competitive manner.